Drivers of the future retailing environment - Siegfried Numberger; Carsten Rennhak (Hochschule Reutlingen, School of International Business (SIB), 2011)
In order to forecast major paradigm shifts in any industry, one needs to understand the driving forces of change. This paper focuses on the retail industry and tries to identify decisive factors which shape this industry's future. Based on the findings of Numberger/Rennhak (2005) a set of variables is derived from roughly fifty semi-structured interviews with retailers and customers as well as academics and from literature. As Numberger (2004) proposed, interviewees were cross-functional and interdisciplinary. The survey included questions about the future medium of shopping, the influence on its development, and general trends and interests with regards to the future. Results were analysed such that variables are aggregated from the text without an a priori framework such as PEST and included if they correlate highly with the entire system and if specific events are highly likely. The challenge of the study is to aggregate the data to few meaningful variables in order to keep complexity low enough enabling a later check of consistency.
urn:nbn:de:bsz:21-opus-58313
Keywords: 650